Serving to different locations: set-up, toss, and racket kinematics of the professional tennis serve - Reid, M.; Whiteside, D.; Elliott, B. (Sports Biomechanics, 2011)
The serve, as the most important stroke in tennis, has attracted considerable biomechanical interest. Of its component parts, the swing has received disproportionate research attention and consequently, little is known regarding toss kinematics. Indeed, the age-old question of whether players serve to different parts of the court from the same toss remains unanswered. Six right-handed professionally ranked players hit first serves (FSs) and second serves (SSs) to three 2 × 1 m target areas reflecting the landing locations of T, body and wide serves, respectively, on the deuce court. A 22 camera, 250 Hz VICON MX motion analysis system captured racket, ball, foot, and hand kinematics. Repeated measures ANOVAs assessed within-player differences in foot, racket, and ball kinematics within the FS and SS as a function of landing location. The positions of the front foot, ball zenith, and ball impact were significantly different in the FS, while kinematics across all SS were consistent. Front foot position was closer to the centre mark in the T FS and players impacted the ball further left in the wide FS compared to the T FS. This study discusses the findings in the context of the development of the serve as well as potential implications for the return.